Organizational Culture Mitigates Lower Ratings of Female Supervisors. (November 2019) - Roebuck, Adam; Thomas, Adrian; Biermeier-Hanson, Benjamin
The present study addresses a lack of literature examining contextual factors when investigating gender norms and leader effectiveness. Supervisor–subordinate dyads were assessed for gender dissimilarity effects on ratings of leadership effectiveness. The effect of organizational culture as a moderating force on these effects was also investigated. Results bolster relational demography theory, such that supervisors who fit existing norms (i.e., male supervisors) were rated higher than supervisors that do not (i.e., female supervisors). However, lower ratings for female supervisors were mitigated by effective organizational cultures.